PROFIL KUALITAS LITERASI SAINS SISWA SMP SE-KABUPATEN PATI - Hikmah Naturasari; Fenny Roshayanti; Atip Nurwahyunani (Universitas PGRI Semarang, 2016)
ABSTRACTThis research is motivated by the low achievement of sciencem literacy of Indonesian students in the participation of the study of The Programe for International Student Assessment (PISA) held every three years by The Organization for Economic Co-operation and Development (OECD). This study aims to determine the quality of science literacy profile of junior high school students. The sample amounted to 356 students of SMP class IX, taken using proportionate stativeied random sampling technique. The Method is test and interview. The tests given using questions obtained from the OECD published PISA issue were published in 2009 specifically for matters related to science content. The results showed that the Literacy Quality of Science Profile of Junior High School Students in Pati Regency belong to low category with percentage of 55%. In the category of moderate percentage obtained by 45% and no students who fall into the high category. As for the achievement of the value of each level, the highest ability of students in answering science literacy questions in the level 1 questions with a total of 49.43 moderate categorized, and the lowest ability of students in answering the questions of science literacy is in level questions 6th with a total of 13.48 is low categorized. The conclusion is the quality of science literacy profile of junior high school students in Pati District is low. Keywords: Profil Quality, Science Literation, SMP Student, ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya capaian literasi sains siswa Indonesia pada partisipasi studi The programe for International Student Assessment (PISA) yang diselenggarakan setiap tiga tahun sekali oleh The Organization for Economic Co-operation and Development (OECD). Penelitian ini bertujuan untuk mengetahui profil kualitas literasi sains siswa SMP se-Kabupaten Pati. Sampel dalam penelitian ini berjumlah 356 siswa SMP kelas IX se-Kabupaten Pati yang diambil dengan menggunakan teknik proportionate statified random sampling. Metode pengambilan data menggunakan metode tes dan wawancara. Tes yang diberikan menggunakan soal PISA yang dipublikasikan oleh OECD diterbitkan tahun 2009 khusus untuk soal-soal yang berkaitan dengan konten sains, serta sudah diterjemahkan ke dalam Bahasa Indonesia. Hasil penelitian menunjukkan bahwa Profil Kualitas Literasi Sains Siswa SMP se-Kabupaten Pati tergolong dalam kategori rendah dengan persentase sebesar 55%. Pada kategori sedang diperoleh persentase sebesar 45% dan tidak ada siswa yang masuk dalam kategori tinggi. Pencapaian nilai setiap levelnya, kemampuan tertinggi siswa dalam menjawab soal literasi sains terdapat pada soal level 1 dengan jumlah nilai 49,43 berkategori sedang, dan kemampuan terendah siswa dalam menjawab soal literasi sains terdapat pada soal level 6 dengan jumlah nilai 13,48 berkategori rendah. Sehingga disimpulkan bahwa profil kualitas literasi sains siswa SMP se-Kabupaten Pati tergolong rendah. Kata Kunci: profil kualitas, literasi sains, siswa SMP